2012
DOI: 10.1089/cyber.2012.0109
|View full text |Cite
|
Sign up to set email alerts
|

Microblogging, Online Expression, and Political Efficacy Among Young Chinese Citizens: The Moderating Role of Information and Entertainment Needs in the Use of Weibo

Abstract: In 2011, China's Internet population reached over half a billion users and the popular Twitter-like social networking service, Weibo, has been adopted by half of the users since its launch in August 2009. Given the potential of the Internet to facilitate a civic culture in the authoritarian state, the use of Weibo and its effects on citizens' political attitudes and behaviors are of important concern. A survey of 499 Weibo users found that intensity of use was related to increased willingness to express opinio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 117 publications
(83 citation statements)
references
References 22 publications
3
74
0
1
Order By: Relevance
“…On the other hand, communications of non-sanctioned information and views, especially through microblogs, are allowed so long as they do not extend to calls for collective mobilization (King et al, 2013). Some studies showed that informational uses of microblogs were related to willingness to talk about politics (Chan et al, 2012) and the ability to post and repost messages allows grievances and criticisms towards the government to quickly achieve critical mass (Fu and Chau, 2014).…”
Section: )mentioning
confidence: 99%
“…On the other hand, communications of non-sanctioned information and views, especially through microblogs, are allowed so long as they do not extend to calls for collective mobilization (King et al, 2013). Some studies showed that informational uses of microblogs were related to willingness to talk about politics (Chan et al, 2012) and the ability to post and repost messages allows grievances and criticisms towards the government to quickly achieve critical mass (Fu and Chau, 2014).…”
Section: )mentioning
confidence: 99%
“…18(p267) Previous research in both American and Chinese contexts has shown that Internet use and political efficacy are related. 19,20 Given the media-rich and interactive features of SNSs, they are particularly suited to facilitate experiential learning and positive reinforcement for those who are politically efficacious.…”
Section: The Internet and Snss In Political And Civic Participationmentioning
confidence: 99%
“…However, microblog services are widely used by Chinese academics. Because of differences in linguistic structure, 140 Chinese characters contain considerably more information than 140 English characters do (Chan, Wu, Hao, Xi, & Jin, 2012). Hence, the microblog provides much space for social interaction.…”
Section: General Discussion and Conclusionmentioning
confidence: 99%